PENGARUH TEKNIK SELF MANAGEMENT UNTUK MENGURANGI PERILAKU OFF TASK SISWA SMK MUHAMMADIYAH 2 PEKANBARU - Wahyuni Ramadhona; Elni Yakub; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effect of self management techniques to reduce off-task behavior of students of Pekanbaru Muhammadiyah 2 Vocational School. This type of research is a quantitative study with an experimental method using the research design One-Group Pretest-Posttest Design. The measuring instrument used in this study is the off task behavior measurement scale consisting of 50 items before the validity, and after the validity is obtained valid items number 31 items with validity of 0,505 and reliability of 0,901. The subjects of this study were 7 students from SMK Muhammadiyah 2 Pekanbaru who were identified as having high levels of off task behavior. The data analysis technique used is non-parametric statistical techniques using the Wilcoxon test. The results of the study proved that the research hypothesis was accepted. For this reason, it can be concluded that there are differences in behavior scores off task before and after being given treatment in the form of self management techniques. From the results of the spearmen rank test it was obtained 0.775 while the correlation coefficient of r2 was 0,600, thus there was an effect of 60% self mangemant technique at Muhammadiyah 2 Vocational School Pekanbaru.Key Words: Self management, off task behavior of students